Purdue Pharma : public relations problems and corporate social responsibility opportunities - Osland, Asbjorn; Clinch, Nanette; Jin, Rachel (London : SAGE Publications: SAGE Business Cases Originals, 2018)
Pain killers are routinely prescribed by physicians to patients who need to manage pain. In spite of the efforts of those active in the field of pain management, addictions and overdoses in the US have hit crisis levels. Purdue Pharma and other pharmaceutical companies that sell opioids have been criticized in the US for contributing to the addiction crisis. A few lawsuits have been settled by Purdue Pharma, the maker of OxyContin, but it has otherwise complied with the law and US Food and Drug Administration regulations. Despite legal compliance, Purdue Pharma's sales and reputation have faltered. As the company looks to expand pain relief sales abroad through its subsidiary, Mundipharma International, the World Health Organization and others have raised concerns about the risk of opioid addiction in the international market. Purdue Pharma needs to restore public perception and brand reputation, and support the management of pain and control of addiction. Corporate social responsibility (CSR) programs are essential to the achievement of such goals. This case questions whether Purdue Pharma's approach of adhering to the regulatory framework without more focus on addiction achieved its goals and asks what the corporation can do to improve CSR and public relations. It suggests that an integrated stakeholder management analysis is required to develop a holistic way of dealing with the company's problems and the addiction crisis.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Purdue Pharma; Mundipharma International; World Health Organization; Public relations; Pharmaceutical industry